2020
DOI: 10.1021/acs.jnatprod.0c00789
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Aromatic Metabolites in the Solitary Tunicate Cnemidocarpa irene

Abstract: Fourteen aromatic metabolites (6–19) were isolated from an aqueous extract of the solitary tunicate Cnemidocarpa irene collected in Hokkaido, Japan. The structures of the metabolites were determined based on the spectroscopic interpretations, including one- and two-dimensional NMR, mass spectra, UV, and circular dichroism data. The biopterin analogue 10 modulated the behavior of mice after intracerebroventricular injection and showed a weak affinity to ionotropic glutamate receptor subtypes. Analyses of fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…An extensive range of metabolites, including amidotaurines 1413–1415 , pterins 1416–1418 and 1419 , guanine 1420 , cytidine analogue 1421 and tyramines 1422–1424 were reported from Cnemidocarpa irene , 686 while specimens of the genus Synoicum afforded new examples of butenolide-containing rubrolides T 1425 , ( Z )-U 1426 and ( E )-U 1427 ( S. kurani ) 687 and the related isocadiolides A–H 1428–1435 and cadiolide N 1436 ( Synoicum sp.). 688 The coelomic fluid of C. irene has been previously reported to exhibit blue fluorescence when irradiated at 365 nm: pterin 1419 was responsible for blood cell fluorescence, while previously reported irenecarboline A was the source of serum fluorescence.…”
Section: Tunicates (Ascidians)mentioning
confidence: 99%
“…An extensive range of metabolites, including amidotaurines 1413–1415 , pterins 1416–1418 and 1419 , guanine 1420 , cytidine analogue 1421 and tyramines 1422–1424 were reported from Cnemidocarpa irene , 686 while specimens of the genus Synoicum afforded new examples of butenolide-containing rubrolides T 1425 , ( Z )-U 1426 and ( E )-U 1427 ( S. kurani ) 687 and the related isocadiolides A–H 1428–1435 and cadiolide N 1436 ( Synoicum sp.). 688 The coelomic fluid of C. irene has been previously reported to exhibit blue fluorescence when irradiated at 365 nm: pterin 1419 was responsible for blood cell fluorescence, while previously reported irenecarboline A was the source of serum fluorescence.…”
Section: Tunicates (Ascidians)mentioning
confidence: 99%
“…This useful property of pterins can see them utilized as fluorophores [ 56 , 57 ] and easily detected as biomarkers for viral infection, inflammation and cancer [ 58 ]. It was also reported that the fluorescence of red blood cells in tunicate, Cnemidocarpa irene, can be attributed to a pterin derivative [ 59 ]. The compounds highlighted in Scheme 2 and Scheme 10 also fluoresce similarly to that of oxidized MPT.…”
Section: Pterin As Fluorophoresmentioning
confidence: 99%
“…Further isolation work resulted in identification of fifteen more aromatics with various structures [53]. These compounds can be categorized into tauroamides [54].…”
Section: Aromatics From Cnemidocarpa Irenementioning
confidence: 99%
“…These compounds commonly contain 2-amino imidazole groups as found in KB343. Zoanthoxantin (53) and pseudozoanthoxantin (54) form 14π aromatic system with liner and angular arrangement of two aminoimidazole via 7-membred ring, respectively. Terrazoanthine (55) also has two aminoimidazole units without fused aromatic system [74].…”
Section: Polyguanidine Alkaloids From Zoanthariansmentioning
confidence: 99%